Application of a potentiometric electronic tongue for assessing phenolic and volatile profiles of Arbequina extra virgin olive oils - Borges, Thays H. (2018)
The capability of determining the phenolic and volatile profiles of olive oils is of major relevance since these compounds are known to greatly influence the gustatory and olfactory positive attributes of olive oils. An electronic tongue with multiple linear regression models was used to evaluate both profiles based on olive oils potentiometric data generated during a single assay. The proposed electronic tongue-chemometric procedure enabled the quantification of flavonoids, phenolic acids and phenol alcohols of Arbequina extra-virgin olive oils with a similar accuracy of UPLC-MS (0.93 ± 0.03≤R2≤0.98 ± 0.08 for the repeated K-fold cross-validation procedure). Also, it was verified that the potentiometric device should not be applied to evaluate volatile compounds in solution (0.80 ± 0.14≤R2≤0.94 ± 0.05 for the repeated K-fold cross-validation procedure), showing a lower accuracy than HS-SPME-GS-MS. The overall satisfactory results showed that electronic tongue could be used as a practical sensing instrument to generate a chemical profile of the compounds known to influence the positive sensory attributes of olive oils.